Manajemen Produksi pada Program Radio Ardan Bandung - Geger Yuniar; Dede Lilis Chaerowati (Bandung Conference Series: Communication Management, 2024)
Abstract. The Nightmare Side program is a program that tells horror stories, it is said that the stories presented are stories based on direct experiences experienced by the listeners. This research uses qualitative methods with a case study approach, constructivism paradigm and data collection techniques, namely by interviews, observation and documentation. In addition, researchers use data validity tests by triangulating sources, techniques and time to achieve accurate checks. The subjects of this research with key informants are those in the production department and broadcasters who hold sustainability management in the Nightmare Side program on Radio Ardan Bandung. The research result of this study is that the Pre-production process carried out by the production management of the Nightmare Side program needs to use a management function that makes planning more mature with all designs can be realized when producing and organizing the teams when running their jobdesk before the broadcast begins. The stages carried out during the production process are principally to visualize the concepts that have been designed from pre-production, so that everything that has been expected from pre-production can be realized when production takes place. Post-production carried out by the production management by supervising the course of the event then there are problems and obstacles that occur when broadcasting such as technical or non-technical obstacles. The strategy of targeting target listeners on Nightmare Side programs must be able to target new listeners by promoting Nightmare Side programs again by making variations of this poster design make new listeners have an interest in listening. Abstrak. Program Nightmare Side adalah program yang menceritakan kisah horror, konon cerita yang disajikan adalah cerita yang berdasarkan pengalaman langsung yang dialami oleh pendengarnya. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus, paradigma konstruktivisme dan teknik pengumpulan data yaitu dengan wawancara, observasi dan dokumentasi. Selain itu, peneliti menggunakan uji keabsahan data dengan triangulasi sumber, teknik dan waktu untuk mencapai pengecekan yang akurat. Subjek penelitian ini dengan key informant ialah pihak yang berada di bagian produksi dan penyiar yang memegang manajemen keberlangsungan dalam program Nightmare Side di Radio Ardan Bandung. Hasil penelitian dari penelitian ini adalah Proses Pra produksi yang dilakukan oleh manajemen produksi program Nightmare Side perlu menggunakan fungsi manajemen yang membuat perencanaan lebih matang dengan semua rancangan dapat terealisasikan ketika produksian dan pengorganisasian para tim ketika menjalankan jobdesknya sebelum siaran dimulai. Tahapan yang dilakukan ketika proses produksi pada prinsipnya adalah untuk menvisualisasikan konsep-konsep yang sudah dirancang dari pra produksi, dengan demikian semua yang telah diharapkan dari pra produksi dapat terealisasikan ketika produksi berlangsung. Pasca produksi yang dilakukan oleh pihak manajemen produksi dengan mengawasi jalannya acara lalu terdapat permasalahan dan kendala yang terjadi ketika siaran seperti kendala teknis ataupun non teknis. Strategi menyasar target pendengar pada program Nightmare Side harus bisa menyasar pendengar baru dengan mempromosikan lagi program-program Nightmare Side dengan membuat variasi dari desain poster ini membuat pendengar baru memiliki minat untuk mendengarkan.